Detention under anti terrorism laws in Malaysia and Nigeria: an expository study on Boko haram suspects - Karumi, Babagana; Shuaib, Farid Sufian (Universitas Muhammadiyah Yogyakarta, 2017)
Terrorism is an organised transnational crime that has the potential danger to the stability and security of nations, and largely a threat to international peace. The rise of terrorist armed groups across the globe has brought about renewed efforts by States to enact legislations that will curtail the harmful activities of terrorists. Detention is one of such effort used in preventing and disrupting the plans of these terrorists. Nations affected by the activities of armed terrorists experienced arrest and detention of suspects, backed with terrorism prevention legislations with the expected aim of safeguarding the national security. Nevertheless, such detentions are often posed with perceived threat of violation of rights. Cases of prolonged detention without trials are alleged, where suspects are kept on unsubstantiated suspicions with denied access to lawyer and family members. The opportunity to challenge these violations and the basis of detention before the court of law are equally denied. The paper, using doctrinal research method examines anti terrorism laws in Malaysia and Nigeria, with particular reference to detention of Boko Haram suspects in Nigeria. The paper concludes with recommendations on the challenges faced by detainees and the need for adequate safeguards on their rights.